A study on the expression of Her2/neu in malignant epithelial ovarian tumors - Amit Kumar Bhardwaj; Vanita Bhaskar; Rashmi Nayak; Anubhav Chandrakar; Vikas Bombeshwar; Vikas Kailashiya (MGM Journal of Medical Sciences)
Background: Ovarian cancer poses a considerable challenge in surgical treatment, often requiring careful and complex approaches. A review of the literature highlights a wide range of Her2/neu overexpression or amplifications in ovarian tumors, with reported rates between 8% and 66%. This variability may be associated with chemotherapy resistance and poor treatment outcomes, thereby playing a significant role in prognosis. Objective: We aimed to study the expression of Her2/neu in malignant epithelial ovarian tumors using immunohistochemistry. Materials and Methods: This descriptive, observational (cross-sectional) study was conducted in the Department of Pathology at Pt. Jawaharlal Nehru Memorial Medical College, Raipur, Chhattisgarh, India, from August 2022 to December 2023, over 18 months. Seventy cases of malignant epithelial ovarian tumors were included. The immunohistochemical analysis assessed the expression pattern of the Her2/neu protein in these tumors. Results: Among the 70 cases, the majority were serous carcinomas (n = 47, 67.2%), with low-grade serous carcinoma (n = 24, 34.3%) being slightly more common than high-grade serous carcinoma (n = 23, 32.9%). Fourteen cases (20%) were mucinous cystadenocarcinomas, and nine (12.9%) were endometrioid carcinomas. The mean age of the study population was 52.58 ± 2.80 years, with the highest proportion of cases (n = 25, 35.7%) observed in the perimenopausal age group (40–50 years). Her2/neu positivity was observed in 15 cases (21.4%) of the 70 malignant epithelial ovarian tumors. Conclusion: Her2/neu protein overexpression was found in 21.4% (n = 15) of cases. No statistically significant association was observed between Her2/neu overexpression and the histological subtype or the age of the patients.